ID: 91. Issue 4 (April 2016) - Zhang, J; Ramadan, A; Griesenauer, B; Li, W; Turner, M; Kapur, R; Hanenberg, H; Paczesny, S; Liu, C; Blazar, B; Tawara, I
Abstract : Allogeneic hematopoietic stem cell transplantation is an important curative therapy for hematological malignancies and other blood disorders, but graft-versus-host disease (GVHD) remains a devastating complication. We previously identified high plasma soluble suppression of tumorigenicity 2 (ST2) as a biomarker of the development of GVHD and death. ST2, also known as the interleukin (IL)-33 receptor, is one of the newest members of the IL-1 receptor family, and its only known ligand is IL-33. Due to alternative splicing, ST2 has two main isoforms: a membrane-bound form (mST2), expressed on hematopoietic cells that promote type 2 helper T (Th2) cell immune responses, and a soluble form (sST2), secreted by non-hematopoietic cells. sST2 acts as a decoy receptor for IL-33, limiting its availability to mST2-expressing cells. Thus, we hypothesized that blockade of the sST2 will free IL-33 for signaling in mST2-expressing T cells [Th2 cells and ST2 + FoxP3 + regulatory T cells (Tregs)], which will attenuate GVHD. First, we found the onset of GVHD symptoms was correlated with a marked increase of plasma ST2 in multiple clinically relevant GVHD murine models, and blockade of sST2 in the peri-transplant period with a neutralizing monoclonal antibody (anti-ST2 mAb) reduced GVHD clinical and histopathological severity and mortality. We identified intestinal stromal cells and T cells as major sources of sST2 during GVHD. ST2 blockade decreased systemic interferon-γ, IL-17, and IL-23 but increased IL-10 and IL-33 plasma levels. ST2 blockade also reduced sST2 production by IL-17–producing T cells while maintaining protective mST2-expressing Th2 cells and Tregs. In addition, ST2 blockade increased the frequency of intestinal myeloid-derived suppressor cells (MDSCs) and decreased the frequency of intestinal CD103 dendritic cells (DCs). Finally, whole transcriptome analysis of T cells comparing anti-ST2 mAb-treated mice versus IgG control-treated mice showed that anti-ST2 mAb administration up-regulated gene expression of cytokines and cytolytic molecules that have been implicated in antitumoral or graft-vs-leukemia (GVL) activity, such as IL-27, IL-18, IL-9, type I interferons, and granzyme A. We therefore postulated that ST2 blockade would not affect therapeutic GVL activity. To confirm this in a clinically relevant GVL model, we developed primary retrovirally induced MLL-AF9 eGFP + leukemic cells on the C3H.SW background. The phenotype of the leukemic cells in this model is eGFP +, CD3 −, B220 − and Mac-1 hi Gr-1 hi . Our results indicated that administration of anti-ST2 mAb or ST2 −/− donor T cells preserved substantial GVL activity and resulted in significantly improved leukemia-free survival. In summary, our findings identify intestinal alloreactive T cells as an important source of the decoy receptor for IL-33 that can be blocked with two doses of anti-ST2 mAb in the peri-transplant period without inhibiting the beneficial mST2 expression on Th2 cells and Tregs or the GVL activity. In addition, ST2 blockade induced expansion of tolerogenic MDSCs while inhibiting immunogenic CD103 DCs during GVHD. This study offers new perspectives on the translation of drug-targetable biomarkers for selectively and safely treating GVHD and other T cell-mediated human disorders.